Semi-analytical modeling of advanced water injection in low permeability reservoirs under non-Darcy-flow condition - Chengyong Li (Advances in Mechanical Engineering, 2019)
Water flooding is widely used to enhance oil recovery in the oilfield. Advanced water injection technology has proven to be an effective method of development for these low permeability reservoirs. Nevertheless, the fluid flow in a low permeability reservoir is governed by non-Darcy flow and the threshold pressure gradient effect. Several efforts have been made experimentally and numerically to design and optimize the field operation parameters. However, it is still challenging to simulate and predict the impact of various injection parameters on well performance in a computationally efficient manner. A simple and efficient semi-analytical model is developed for advanced water injection which considers non-Darcy flow and threshold pressure effects. The stimulated reservoir volume can be evaluated by calculating the pressure gradient distribution. The impact of water injection rate, total injection volume, and injection time on stimulated reservoir volume is investigated. Finally, a field-scale numerical simulation and experiment are conducted to validate the proposed model. This model provides reservoir engineers a simple and accurate tool for predicting, evaluating, and optimizing the advanced water injection operation practices.